ANALYSIS OF THE UNESCO PILLARS OF EDUCATION IN COSMETOLOGY, ETHNOBEAUTY, AND WELLNESS LEARNING: A LEARNING THEORY PERSPECTIVE IN HIGHER EDUCATION - Rosi Titiana Dinar Pangesti Rahayu; Sri Usodoningtyas; M Mamduh Winangun (Adornata : Ethnobeauty and Wellness Journal, 2026)
This article analyzes the relationship between the four pillars of UNESCO education and learning theories in the context of cosmetology, ethnobeauty, and wellness learning in higher education. The four pillars of education introduced by UNESCO, namely learning to know, learning to do, learning to be, and learning to live together, provide a holistic framework for developing students’ knowledge, practical skills, personal identity, ethical awareness, and social responsibility. This article uses a qualitative approach with a literature study method by reviewing books, journal articles, and educational reports related to UNESCO’s educational pillars, learning theory, cosmetology education, ethnobeauty, natural beauty practices, and wellness-oriented learning. The findings show that learning to know is aligned with cognitivism because it emphasizes mental processes and conceptual understanding; learning to do is aligned with behaviorism because it emphasizes practice, repetition, and skill formation; learning to be is aligned with humanistic theory because it emphasizes self-development, professional identity, and ethical responsibility; and learning to live together is aligned with social constructivism because it emphasizes interaction, collaboration, and cultural understanding. In the context of beauty and wellness education, these four pillars can guide learning that integrates scientific knowledge, technical competence, cultural beauty values, client-centered care, and sustainable beauty practices. Therefore, the UNESCO pillars and learning theories can be used as a theoretical foundation for developing holistic, culturally responsive, and professionally relevant cosmetology education.